The Distinction Between False Dilemma and False Disjunctive Syllogism - Tomic, Taeda (Informal Logic)

(untitled) (Informal Logic, 2021)
Since a clear account of the fallacy of false disjunctive syllogism is missing in the literature, the fallacy is defined and its three types are differentiated after some preliminaries. Section 4 further elaborates the differentia specifica for each of the three types by analyzing relevant argument criticism of each, as well as the related profiles of dialogue. After defining false disjunctive syllogisms, it becomes possible to distinguish between a false dilemma and a false disjunctive syllogism: section 5 analyzes their similarities (which explains why the fallacies are often confused with one another) and section 6 explains their differences.